Opinions of the Nursing Students on Ageism - Tülay Demiray; Ümran Dal Yılmaz (İstanbul Medical Journal, 2017)

(untitled)
Objective: To determine the opinions of nursing students on ageism and their thoughts regarding working with elderly individuals after graduation.Methods: This descriptive study was conducted in the academic year 2014–2015 and included 175 student volunteers, of whom 114 were firstgrade students and 61 were fourth-grade students studying in the Nursing Department, School of Health Sciences, Near East University. The Personal Information Form and Ageism Attitude Scale (AAS) were used for collecting data, which were assessed using the SPSS 20.0 statistics package program (Statistical Package of Social Sciences, v. 20.0 Chicago, IL, USA). The chi-square test was used for cross tables, and the t-test was used for comparing two-choice questions of the scale in the independent groups; single direction variance analysis was used for analyzing variables with more than one choice.Results: The attitudes of students in terms of elderly discrimination were positive, and the average AAS score was 79.56±9.39. The average total AAS score and average total score of the “negative discrimination against the elderly” sub-scale of the first-grade students were lower than those of the fourth-grade students (p<0.05). For all students, a statistically significant difference (p<0.05) was determined between the “working with the elderly individual” status and the “negative discrimination against the elderly” sub-scale. For all students, a statistically significant difference was determined between the “living with parents in the future” status and the “working with the elderly in the future” status (p<0.05).Conclusion: Nursing students have a positive attitude toward elderly discrimination. The data suggests that, during their last academic year, nursing students should be educated about attitudes toward the elderly, and they should be given the opportunity to work with elderly individuals.